2018
DOI: 10.1371/journal.pone.0199654
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width at hospital discharge and out-of hospital outcomes in critically ill non-cardiac vascular surgery patients

Abstract: ObjectiveRed cell distribution width (RDW) is associated with mortality and bloodstream infection risk in the critically ill. In vascular surgery patients surviving critical care it is not known if RDW can predict subsequent risk of all-cause mortality following hospital discharge. We hypothesized that an increase in RDW at hospital discharge in vascular surgery patients who received critical care would be associated with increased mortality following hospital discharge.Design, setting, and participantsWe perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Red cell distribution width (RDW) is increased in response to inflammatory stimuli ( 9 ), and increased RDW is reported to be associated with unfavorable outcomes in many inflammatory diseases, such as pneumonia ( 32 ), sepsis ( 33 ), and ARDS ( 34 ). Previous studies have reported a positive association between RDW and all-cause mortality of many critically ill conditions ( 35–37 ). The elaborated mechanisms of RDW increase in critically ill patients remain to be determined; inflammation is induced to generate premature erythrocytes of premature erythrocytes from the bone marrow ( 38 ).…”
Section: Discussionmentioning
confidence: 95%
“…Red cell distribution width (RDW) is increased in response to inflammatory stimuli ( 9 ), and increased RDW is reported to be associated with unfavorable outcomes in many inflammatory diseases, such as pneumonia ( 32 ), sepsis ( 33 ), and ARDS ( 34 ). Previous studies have reported a positive association between RDW and all-cause mortality of many critically ill conditions ( 35–37 ). The elaborated mechanisms of RDW increase in critically ill patients remain to be determined; inflammation is induced to generate premature erythrocytes of premature erythrocytes from the bone marrow ( 38 ).…”
Section: Discussionmentioning
confidence: 95%
“…DRG type was defined as medical or surgical and incorporates the Diagnostic Related Grouping (DRG) methodology, devised by the Centres for Medicare & Medicaid Services and is reflective of case mix and resource utilization [ 21 23 , 30 ]. Ethnicity was either self-determined or designated by a patient representative/healthcare proxy.…”
Section: Methodsmentioning
confidence: 99%
“…Patients eligible for inclusion were hospitalized adults aged ≥18 years who were admitted to intensive care unit (ICU) or in-patient care ward and who underwent non-cardiac vascular surgery during their hospitalization and survived to hospital discharge. All patients were assigned at least one Current Procedural Terminology (CPT) code for vascular surgery [ 23 ] ( S1 File ), and were assigned a Diagnostic Related Group (DRG) code. Patients treated with open vascular surgery as well as endovascular procedures were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous cohort of critically ill vascular surgery patients (n = 4715), the post-discharge mortality in ICU survivors was studied 37 . From these data it was assumed that 90-day post-discharge mortality was 7.5%.…”
Section: Power Calculations and Statistical Analysismentioning
confidence: 99%